Meningkatkan Profesionalisme Berbasis Teknologi dan Empati untuk Mendukung Pengabdian Masyarakat di Era Society 5.0 - Ni Putu Gatriyani (Komunikasi, 2024)
The Society 5.0 era demands synergy between the advancement of intelligent technologies and human values to create an inclusive and sustainable society. In the context of community service, technology-driven and empathy-based professionalism becomes a key strategy to address the complexities of modern societal needs. Professionalism supported by digital literacy, artificial intelligence, and big data analysis enables more effective innovative solutions. However, technology must be accompanied by an empathetic approach that places humans at the center, ensuring every intervention is relevant to local needs and contributes to collective well-being. Through this theme, presented via a national webinar, community service programs are directed towards enhancing adaptive skills, critical thinking, and lifelong learning while promoting the values of empathy and collaboration. The Bali Lecturer Communication Forum organized a national webinar aimed at equipping participants—academics, practitioners, and the general public—with relevant knowledge and skills to utilize technology in addressing modern challenges and to foster the development of human resources that are not only professionally competent but also socially compassionate. The program aspires to create community services that strengthen empathy and humanity, emphasizing the importance of empathy in utilizing technology to understand and meet societal needs more personally and effectively. Multidisciplinary collaboration is encouraged, inviting professionals from various fields to synergize and create greater impact in community service. All innovations and services are directed to support sustainable development, striking a balance between technological innovation and humanistic approaches to maximize social impact in the Society 5.0 era.